Management of patients with chronic rhinosinusitis with nasal polyps in Spain: learnings from a nationwide survey of otorhinolaryngologists - Alobid, Isam; Liesa, Rafael Fernández; Aubá, Jose Miguel Villacampa; Moure, Abraham L.; Sánchez-Herrero, M. Guadalupe; del Cuvillo Bernal, Alfonso (European archives of oto-rhino-laryngology, 2024)
Purpose To describe the self-reported practices on the diagnosis, treatment, and follow-up of patients with chronic rhinosinusitis with nasal polyps (CRSwNP) by ear, nose, and throat (ENT) specialists in Spain to identify potential areas for management optimization. Methods A cross-sectional online survey with 16 questions was carried out. Recruitment was performed by emailing registered ENT specialists in the Spanish Society of Otorhinolaryngology and Head and Neck Surgery (SEORL-CCC). Results In total, 127 ENT specialists completed the survey. Fifty-one percent of respondents combined clinical criteria and objective evidence of mucosal inflammation to diagnose CRSwNP. Patient interview and, to a lower degree, a visual analogue scale were the most employed diagnostic tools to quantify symptom severity. Less than half (45%) routinely used the 22-item sino-nasal outcomes test (SNOT-22) to assess the impact of CRSwNP disease in quality of life. The use of patient-reported outcomes and other clinical evaluation tools showed a larger uptake among ENT specialists that worked at an ENT department with an available rhinology unit. Almost all the specialists surveyed (95%) recommended biological treatment, particularly in patients with uncontrolled CRSwNP with respiratory comorbidities (76%), as well as in candidates for revision surgery (66%). Conclusion Spanish otorhinolaryngologists showed a trend toward incorporating CRSwNP guideline recommendations in their clinical practice. The observed low uptake of patient-reported outcomes and objective clinical evaluation tools in routine clinical practise have been identified as areas for optimizing the management of patients with CRSwNP.